PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI STARBUCKS COFFEE DISTRICT 23 JAKARTA - Lestari Pasaribu (JURNAL KONSISTEN, 2024)
Purpose. This study aims to determine the positive and significant influence of motivation variables on employee performance, to determine the positive and significant influence of training variables on employee performance and to determine the positive and significant influence of training and motivation variables simultaneously on employee performance at Starbucks Coffee District 23 Jakarta. Methods. The method used in this study is the quantitative method. The sample used is a saturated sample technique totaling 84 employees. Data collection techniques through primary and secondary data. simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and f test. Findings. The value of